Pengaruh Nikotin dalam Rokok Elektrik Terhadap Kadar MDA dan SOD pada Darah Tikus - Nufus, Izzatun; Lisdiana, Lisdiana; Marianti, Aditya; Peniati, Endah (Universitas Negeri Semarang, 2020)
Electric cigarettes are cigarettes that operate with battery power to burn liquids to produce steam. One ingredient of electric cigarettes that is the same as that in tobacco cigarettes is nicotine. Nicotine is a substance that can cause a person to become addicted, so if a person consumes continuously the body can experience oxidative stress. This is indicated by an increase in MDA levels and a decrease in SOD levels. This study aims to determine the effect of nicotine in e-cigarettes on MDA and SOD levels in blood. The study was conducted on 30 male white rats of the Wistar strain divided into 5 groups, namely the control group (-), control (+), KP1 (electric cigarette with nicotine 3mg) and KP2 (electric cigarettes with nicotine 6mg), and KP3 (cigarettes electric with nicotine 9mg) and exposure to cigarette smoke for 30 days. Data were analyzed by non parametric kruskal wallis and Man Whiteney tests for MDA levels and one way anova test and LSD further testing for SOD levels. The results of the statistical analysis showed that MDA and SOD levels in the control group (-) were significantly different from all groups. The conclusion of this study is that nicotine has an effect on increasing MDA levels and decreasing SOD levels. Rokok elektrik merupakan rokok yang beroperasi dengan tenaga baterai untuk membakar cairan sehingga menghasilkan uap. Salah satu kandungan dari rokok elektrik yang sama dengan yang ada di rokok tembakau adalah nikotin. Nikotin merupakan suatu zat yang dapat menyebabkan seseorang menjadi kecanduan, sehingga jika seseorang mengonsumsi terus menerus maka tubuh dapat mengalami stress oksidatif. Hal ini ditandai dengan adanya peningkatan kadar MDA dan penurunan kadar SOD. Penelitian ini bertujuan untuk mengetahui pengaruh nikotin dalam rokok elektrik terhadap kadar MDA dan SOD pada darah. Penelitian dilakukan pada 30 ekor tikus putih jantan galur Wistar yang dibagi menjadi 5 kelompok, yaitu kelompok kontrol (-), kontrol (+), KP1 (rokok elektrik dengan nikotin 3mg) dan KP2 (rokok elektrik dengan nikotin 6mg), dan KP3 (rokok elektrik dengan nikotin 9mg) dan paparan asap rokok selama 30 hari. Data dianalisis dengan uji non parametric kruskal wallis dan Man Whiteney untuk kadar MDA dan uji one way anova dan uji lanjut LSD untuk kadar SOD. Hasil analisis statistik menunjukkan kadar MDA dan SOD pada kelompok kontrol (-) berbeda nyata dengan semua kelompok. Simpulan dari penelitian ini adalah nikotin berpengaruh pada peningkatan kadar MDA dan penurunan kadar SOD